STUDI KELAYAKAN EKONOMI PENGEMBANGAN APLIKASI PEMINJAMAN RUANGAN DI UNIVERSITAS PERTAMINA - Muhammad Deta Aditya; Meredita Susanty; Muhammad Rizky Widyayulianto; Fitri Karimah; Akhmal Rizkyanto; Marrosandy Bagus Saputra (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2019)
Waste are serious environmental issues in Indonesia. To minimize waste, there have been efforts by companies to reduce the amount of paper used. For example, in Universitas Pertamina there has been idea to make a new application-based system to rent a room, replacing the old system that still produce waste such as paper and ink bottle. Before making the application, there should be an economic feasibility study to determine whether this application can be made from economy aspects. To conduct this study, quantitative method was used, as well interview and literature studies to gather data. From that, the estimation of cost for existing room renting system is Rp98.609.423,30. Meanwhile, the estimation of cost needed to make an application for room renting system is Rp15,254,680.00 and the cost to run the system is Rp48.840.856,30. From data collected above, it says that payback period from the development of the application is less than a year, so the development of application of room renting is feasible in the economical aspect.